Odškodninska odgovornost članov poslovodstva - analiza nekaterih sodb Vrhovnega sodišča RS - Podgorelec, Peter (Podjetje in delo, 2013)
The paper analyses some of the most significant judgements of the Supreme Court of the Republic of Slovenia pertaining to liability for damages of the members of the management board. The recent increase in the number of actions for damages in the country makes it an increasingly relevant issue. The author of the paper finds that the analysed judgements are generally compliant with legal theory positions. Problematic is only the view of the Supreme Court that the liability of directors for the annual report constitutes liability for the result. The author also provides a short presentation of liability regulations and points out some of its deficiencies.
Keywords: člani; gospodarske družbe; odškodninska odgovornost; reševanje; Slovenia; Slovenija; sodišča; sodne odločbe; spori; uprava; vodenje